2015
DOI: 10.4137/bmi.s22434
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tyrosine Kinase Inhibitors in Indolent and Other Mature B-Cell Neoplasms

Abstract: Targeting tyrosine kinases represents a highly specific treatment approach for different malignancies. This also includes non-Hodgkin lymphoma since it is well known that these enzymes are frequently involved in the lymphomagenesis. Hereby, tyrosine kinases might either be dysregulated intrinsically or be activated within signal transduction pathways leading to tumor survival and growth. Among others, Bruton’s tyrosine kinase (Btk) is of particular interest as a potential therapeutic target. Btk is stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…The activation (by tyrosine phosphorylation) of BTK may stimulate the nuclear factor (NF)-κB and mitogen-activated protein kinase (MAPK) signaling pathways, and ultimately trigger a series of inflammatory reactions ( 14 18 ). Previous studies have reported that BTK inhibition may be efficient in controlling B cell malignancy and B cell-related autoimmune disorders ( 19 23 ); however, whether BTK participates in THS-induced lung injury remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The activation (by tyrosine phosphorylation) of BTK may stimulate the nuclear factor (NF)-κB and mitogen-activated protein kinase (MAPK) signaling pathways, and ultimately trigger a series of inflammatory reactions ( 14 18 ). Previous studies have reported that BTK inhibition may be efficient in controlling B cell malignancy and B cell-related autoimmune disorders ( 19 23 ); however, whether BTK participates in THS-induced lung injury remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations can dysregulate SYK activity, leading to aberrant proliferation, survival, and differentiation of B-cells, which play a pivotal role in the development and activation of these cells. Consequently, these alterations contribute to the development of hematological cancers ( Kutsch et al, 2015 ). Common tyrosine kinase inhibitors (TKIs) marketed or in the progress of clinical trials in HMs treatment are shown in Table 1 .…”
Section: The Clinical Regimens For the Treatment Of Hmsmentioning
confidence: 99%